Protein Translocase of Mitochondrial Inner Membrane in Trypanosoma brucei - Singha, Ujjal K. (American Society for Biochemistry and Molecular Biology, 2012)
Translocases of mitochondrial inner membrane (TIMs) are multiprotein complexes. The only Tim component so far characterized in kinetoplastid parasites such as Trypanosoma brucei is Tim17 (TbTim17), which is essential for cell survival and mitochondrial protein import. Here, we report that TbTim17 is present in a protein complex of about 1,100 kDa, which is much larger than the TIM complexes found in fungi and mammals. Depletion of TbTim17 in T. brucei impairs the mitochondrial import of cytochrome oxidase subunit IV, an N-terminal signal-containing protein. Pretreatment of isolated mitoplasts with the anti-TbTim17 antibody inhibited import of cytochrome oxidase subunit IV, indicating a direct involvement of the TbTim17 in the import process. Purification of the TbTim17-containing protein complex from the mitochondrial membrane of T. brucei by tandem affinity chromatography revealed that TbTim17 associates with seven unique as well as a few known T. brucei mitochondrial proteins. Depletion of three of these novel proteins, i.e. TbTim47, TbTim54, and TbTim62, significantly decreased mitochondrial protein import in vitro. In vivo targeting of a newly synthesized mitochondrial matrix protein, MRP2, was also inhibited due to depletion of TbTim17, TbTim54, and TbTim62. Co-precipitation analysis confirmed the interaction of TbTim54 and TbTim62 with TbTim17 in vivo. Overall, our data reveal that TbTim17, the single homolog of Tim17/22/23 family proteins, is present in a unique TIM complex consisting of novel proteins in T. brucei and is critical for mitochondrial protein import.